An Institutional and Opinion Analysis of Colorado's Hydraulic Fracturing Disclosure Policy. Issue 2 (4th March 2017) - Weible, Christopher M.; Heikkila, Tanya; Carter, David P.
Abstract: Hydraulic fracturing and oil and natural gas development are possibly the most contentious energy and environmental issues to face the USA in the twenty-first century. One point of contention is the disclosure of fluids used in the hydraulic fracturing process. This paper analyses the Colorado 2011 policy requiring disclosure of hydraulic fracturing fluid information, considered one of the first comprehensive hydraulic fracturing disclosure policies in the country. We conduct an institutional analysis of the disclosure policy to understand how the policy establishes information flows and grants and restricts choices by targeted actors. We then analyse the opinions of people actively involved in hydraulic fracturing debates in Colorado to assess whether they view the disclosure policy as resolving problems. The institutional analysis illustrates how the policy allocates responsibilities in sending and receiving information and the opinion survey shows divergence in perceptions of its potential to resolve problems associated with chemical use or disclosure. Most respondents are in agreement that the new policy failed to build public trust of the hydraulic fracturing process.